2009
DOI: 10.1080/07434610802131059
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Aided Language Stimulation: Does it Increase AAC Use with Adults with Developmental Disabilities and Complex Communication Needs?

Abstract: A single subject ABAB design was used to determine the efficacy of aided language stimulation to teach the use of AAC techniques to adults with developmental disabilities. Sixteen participants were divided into two equal groups. In each group, half of the participants were able to communicate functionally using spoken language and half had complex communication needs and did not have functional, symbolic communication systems. Each group met twice weekly for 30 min per session. Researchers modeled the use of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 8 publications
(7 reference statements)
0
40
0
Order By: Relevance
“…Whilst the use of symbols with adults with more moderate to severe learning disabilities is quite well documented (e.g., Beck et al . ), we found no specific reference to the approach with children and adults with PMLD although the definition of PMLD used in this paper does not preclude some level of symbolic functioning.…”
Section: Introductionmentioning
confidence: 72%
“…Whilst the use of symbols with adults with more moderate to severe learning disabilities is quite well documented (e.g., Beck et al . ), we found no specific reference to the approach with children and adults with PMLD although the definition of PMLD used in this paper does not preclude some level of symbolic functioning.…”
Section: Introductionmentioning
confidence: 72%
“…Augmented input may also support expressive language skills. By observing partners' use of AAC/KWS, individuals with intellectual disabilities may acquire AAC/KWS skills (e.g., Beck, Stoner, & Dennis, 2009;Dodd & Gorey, 2014;Faw, Reid, Schepis, Fitzgerald, & Welty, 1981;Meuris, et al 2014). When staff consistently provide augmented input, clients are also more inclined to generalize AAC/KWS skills to other settings (Dodd & Gorey, 2014;Schepis et al, 1982).…”
Section: Staff Use Of Abstractigningmentioning
confidence: 97%
“…In an experimental case study, Harris and Reichle (2004) showed that aided language stimulation had a positive impact on the symbol comprehension and production of three preschool-aged children with developmental disabilities. Other studies have investigated similar interventions and, although the results differ to some extent among the participants, improvements in language comprehension and expressive abilities have been demonstrated for both children and adults (e.g., Beck, Stoner, & Dennis, 2009;Binger & Light, 2007;Bruno & Trembath, 2006;Drager et al, 2006; see also Dada, Granlund, & Alant, 2007). To summarize, when the communication partner practices aided language stimulation and uses graphic symbols, the beginning communicator is shown how and for what purposes AAC can be used.…”
Section: Introductionmentioning
confidence: 94%